A preliminary report of successful cleavage after calcium ionophore activation at ICSI in cases with previous arrest at the pronuclear stage. Issue 6 (December 2015) - Darwish, Ehab; Magdi, Yasmin
Abstract: Artificial oocyte activation (AOA) has been previously suggested as a means to overcome the problem of total fertilization failure, which affects about 1–3% of the intracytoplasmic sperm injection (ICSI) cycles. A preliminary study on the application of chemical AOA was conducted using A23187 Ca 2+ ionophore to improve embryonic development in four women with a history of complete fertilization arrest and inability to transit to cleavage stage during previous ICSI trials. Data indicated that activated oocytes resulted in better fertilization, embryonic development and clinical pregnancy in one of the four couples. Therefore, ICSI combined with AOA using Ca 2+ ionophore may be useful in selected patients with cleavage failure, and may help the zygotes to reach more advanced developmental stages.